Which are the strategies preferred by young people to negotiate the use of condoms? - Montserrat Planes; M.E. Gras; A.B. Gómez (INFAD, 2018)
We evaluate the perception of the adequacy of different strategy types to achieve the use of condoms whit a romantic partner in a sample of undergraduate Psychology students (81.4% women, mean age = 21 years, sd = 2.8). Assessments were made with a scale from 0 (not adequate) to 10 (totally adequate). The results show that young people consider more appropriate strategies involving a more or less direct requirement (average 8.51, sd = 1.15) followed by those that consider the protection provided by the condom (mean 8.13, sd = 1.96), whereas the least adequate strategies are those involving emotional arguments (mean 6.32 sd = 2.27). These results should be considered in planning interventions to promote the use of condoms among young people.